Summative assessment planning in the Kurikulum Merdeka on two-dimensional figure materials - Mar’atu Sholikhah; Yulia Maftuhah Hidayati (Inovasi Kurikulum, 2024)
Summative assessment is part of Kurikulum Merdeka which is expected not to be put aside because it has an important influence in determining students' final grades or grade promotion. This research aims to analyze summative assessment planning in Kurikulum Merdeka on plane material. The research method used is qualitative. There are three subjects of this research, namely the school principal, mathematics teacher, and homeroom teacher. Research data collection techniques are interviews and documentation. The data that has been collected is analyzed, starting with data reduction, data presentation, and conclusions. The results of the research analyzed the planning of summative assessment of scope material, namely the teacher gave questions about the area perimeter of triangles and parallelograms, the area of rectangles, trapezoids, and kites, while the assessment technique used essays. In the mid-semester summative assessment, the teacher gives questions about the area perimeter of a triangle, the area parallelogram, the area square, and the perimeter of a rectangle. In the end-of-semester summative assessment, the teacher gave questions about the area of the perimeter of a square and rectangle, the area of a trapezoid, the area of a triangle, and the perimeter of a parallelogram. The assessment techniques used are multiple-choice, essay, and essay questions.   Abstrak Asesmen sumatif menjadi bagian dari kurikulum merdeka yang diharapkan untuk tidak dikesampingkan dikarenakan Asesmen Sumatif memiliki pengaruh penting dalam menentukan nilai akhir atau kenaikan kelas peserta didik. Penelitian ini bertujuan untuk menganalisis tentang perencanaan asesmen sumatif dalam kurikulum merdeka pada materi bangun datar. Metode penelitian yang digunakan kualitatif. Subyek penelitian ini ada tiga yaitu kepala sekolah, guru matematika dan wali kelas. Teknik pengumpulan data penelitian ialah wawancara dan dokumentasi. Data yang telah dikumpulkan dilakukan analisis data mulai dari reduksi data, penyajian data, dan kesimpulan. Hasil penelitian menganalisis tentang perencanaan Asesmen sumatif lingkup materi yaitu guru memberi soal tentang luas keliling segitiga dan jajargenjang, luas persegi panjang, trapesium dan layang-layang sedangkan teknik penilaian menggunakan essay. Asesmen sumatif tengah semester, guru memberikan soal tentang luas keliling segitiga, luas jajargenjang, luas persegi dan keliling persegi panjang. Asesmen sumatif akhir semester, guru memberi soal tentang luas keliling persegi dan persegi panjang, luas trapesium, luas segitiga, dan keliling jajargenjang. Teknik penilaian yang digunakan yaitu pilihan ganda, essay dan soal uraian. Kata Kunci: Asesmen sumatif: bangun datar; Kurikulum Merdeka; rencana asesmen